2021
DOI: 10.1186/s12889-021-11915-1
|View full text |Cite
|
Sign up to set email alerts
|

Job crafting promotes internal recovery state, especially in jobs that demand self-control: a daily diary design

Abstract: Background Research on how employees recover from work has focused primarily on recovery during non-work hours (external recovery) rather than recovery during work hours (internal recovery). Using the conservation of resources theory as a conceptual framework, we tested whether job crafting promotes an internal recovery state, and examined the processes that explain this association. Methods Using the daily diary method, 120 full-time employees pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Additionally, other studies refer to the protective function of job crafting for employees’ mental health, e.g. by reducing exhaustion [ 25 , 29 , 30 ]. If the categories are integrated in the JDR model, the blurred work and life domains impact employees as a job demand when WFH, while boundary management and energy resources management can function as strategies to reduce exhaustion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, other studies refer to the protective function of job crafting for employees’ mental health, e.g. by reducing exhaustion [ 25 , 29 , 30 ]. If the categories are integrated in the JDR model, the blurred work and life domains impact employees as a job demand when WFH, while boundary management and energy resources management can function as strategies to reduce exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…In general, job crafting behavior has been found to be a protective factor for employees’ mental health [ 25 ] due to the reduction of psychological distress [ 22 , 26 ], burnout [ 27 , 28 ], and exhaustion [ 29 , 30 ]. For an overview of the positive outcomes of job crafting on employees’ health and mental health such as effects on well-being, resilience, vitality, reduced fatigue, reduced distress [ 13 , 14 ].…”
Section: Job Demands-resources Model (Jd-r Model) and Job Craftingmentioning
confidence: 99%
“…While recent diary studies about crafting (i.e., Demerouti et al, 2019; Shi et al, 2021) have contributed to our understanding of day-level crafting and its associations with day-level well-being outcomes, little is known about crafting patterns unfolding over the course of the day.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…According to the conservation of resources (COR) theory [ 47 ], people have the motivation to obtain, retain and protect resources. Shi and colleagues [ 48 ] showed that employees’ job crafting efforts can help to obtain and protect their resources during the workday which positively predicted their after-work energy levels. During off-job time, less or even no job demands are present and people are able to freely make decisions regarding their off-job time.…”
Section: Theory and Hypothesesmentioning
confidence: 99%